How Efficient Are Monte Carlo Calculations Together With the Q-System to Determine Radioactive Transport Limits? Case Study on Medical Radionuclides - Maietta, Maddalena; Haddad, Ferid; Avila, Sebastien (Frontiers in Medicine, 2022)
The development of the so-called theranostics approach, in which imaging information are used to define a personalized therapeutic strategy, is driving the increasing use of radionuclides in nuclear medicine. Each radionuclide has its own way of production. They are generally extracted from stable or radioactive target bombarded with a particle beam. After extraction/purification of the target, the radionuclides, either implanted on solid or in liquid form, needs to be transported to a centralized production site, a radiopharmacy or an hospital. The transport of needed radioactive material must obey strict rules define under the supervision of IAEA. For a radionuclide, a limit in activity that it is possible to transport has been established for each type of allowed packages.For type A package these limits are called A1 (for special form sources, i.e. certified perfectly sealed and encapsulated sources) and A2 (for non-special form sources). However, these limits can be easily reached if the activity to transport is high or if the radionuclide of interest is a “non-conventional” one. Indeed, for many radionuclides, there are no available/tabulated A1 and A2 and, in these cases, a very conservative set of values is imposed. This is in particular the case for some of the non-conventional radionuclide of interest in medicine (as for example Tb-149 or Tb-161). The non-tabulated values, and in general the A1/ A2 limit, can be evaluated following the so-called Q-system and using Monte-Carlo calculations. In the present work, we have used the MCNPX Monte Carlo code to evaluate dose rate values in different regulatory scenarios. This has allowed us to determine A1/ A2 coefficients for several non-conventional radionuclides of interest for medical applications. The developed technique can be extended easily to other radionuclides and can be adapted in case of changes in regulatory rules.